Original articleDisturbed regulation of the isolated middle cerebral artery in acute hyponatremia - Aleksandrowicz, Marta; Koźniewska, Ewa (Folia Neuropathologica, 2013)
Hyponatremia is a common disorder of water-electrolyte balance characterized by the decrease of plasma sodium ions concentration below 135 mM. Although water-electrolyte balance is regulated by a kidney, symptoms of hyponatremia are related to the disturbances of intracranial homeostasis and are attributed to brain swelling. Despite the importance of blood vessels function for the homeostasis of the brain, little is known about the influence of hyponatremia on cerebrovascular regulation. In the present study isolated, perfused and pressurized rat middle cerebral arteries (MCAs) were subjected to hyponatremia in the organ chamber by lowering the concentration of sodium ions from 145 to 121 mM. The response of the MCAs to the changes in intravascular pressure and to endothelium-dependent and independent vasodilators was compared in normo- and hyponatremia. The following results were obtained: the contraction of the MCA during progressive increases in intravascular pressure was similar in normo- and hyponatremia; the dilation in response to acetylcholine (10-6 M, 10-5 M and 10-4 M), which is endothelium- and nitric oxide-dependent, was severely impaired in hyponatremia; the contraction after administration of the nonselective inhibitor of nitric oxide synthesis – NG-nitro-L-arginine methyl ester (L-NAME, 10-5 M) was similar in normo- and hyponatremia; the nitric oxide donor – S-nitroso-N-acetylpenicillamine (SNAP, 10-5 M) dilated MCA only in normonatremia. The results of this study show that myogenic response and shear stress-dependent relaxation of the MCA are not affected by acute hyponatremia. However, agonist-stimulated, endothelial nitric oxide synthase (eNOS)-mediated relaxation is severely impaired which is associated with a decreased smooth muscle response to nitric oxide (NO). In conclusion, our results demonstrate that the regulation of isolated middle cerebral artery is impaired in acute hyponatremia which may contribute to the disturbance of intracranial homeostasis associated with hyponatremia.